Implementation of Learning Models in Science and Islamic Education Subjects at SMAN 10 Tangerang City - Nana Herdiana Abdurrahman; Abdul Holik; Zainal Abidin; Euis Dewi Wijayanti; Selamat Selamat; Nina Rahmi (PT Mattawang Mediatama Solution, 2024)
The use of learning models has an essential role, of course it needs to be paid attention to in learning. For this reason, this research aims to explore the learning model applied to Natural Sciences (IPA) and Islamic Religious Education (PAI) subjects at SMA Negeri 10 Tangerang City. This research uses a qualitative approach, case study method. The results of the research show that the learning models implemented within the framework of the Independent Curriculum have been implemented in this school since March 2023. The most interesting finding in this research is that although in general the learning models applied in the classroom are practically almost the same, however There are still differences in nuances between the learning models applied to Natural Science (IPA) subjects and Islamic Religious Education (PAI) subjects. These two differences were divided into two groups, namely the group that used an inquiry-based learning model for science and the group that used a discussion-based learning model for PAI. The learning model in science subjects mainly often uses contextual learning and quantum learning, while the most commonly used learning model in PAI subjects is mind mapping. Teachers at this school have also implemented the use of digital media platforms which can increase the enthusiasm for the learning atmosphere. This small research discusses the implementation of the model for these two subjects because they have a causal relationship, where natural science will bring students to the realm of reason, while Islamic religious science will bring them to the realm of faith, naqli knowledge so that in the end they become human beings. completely.